CONCEPTS: HEALTH / QUALITY OF LIFE / BODY MASS INDEX / HIP WAIST RATIO AND MEASUREMENTS AND CALCULATIONS FOR THE WELFARE (Fiep Bulletin - online, 2014)
The concept of health formulated at the VIII National Health Conference (CNS VIII), held in Brasilia in 1986. Also known as 'expanded concept' health was the result of intense mobilization, which was established in several countries in Latin America during the 1970s and 1980s as a response to authoritarian regimes and the crisis of public health systems. The concept of the WHO, released the letter early April 7, 1948 (since the World Health Day), implying recognition of the right to health and the state's obligation to protect and promote health. It is expected that article, will contribute with regard to the concepts of health and quality of life as well as identify measures BMI and WHR.
Keywords: Health; Quality of Life; Body Mass Index.